Outcome measures in a combined exercise rehabilitation programme for adults with COPD and chronic heart failure: A preliminary stakeholder consensus event. (6th September 2019) - Jones, Amy V; Evans, Rachael A; Man, William D-C; Bolton, Charlotte E; Breen, Samantha; Doherty, Patrick J; Gardiner, Nikki; Houchen-Wolloff, Linzy; Hurst, John R; Jolly, Kate; Maddocks, Matthew; Quint, Jennifer K; et al.
Combined exercise rehabilitation for chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF) is potentially attractive. Uncertainty remains as to the baseline profiling assessments and outcome measures that should be collected within a programme. Current evidence surrounding outcome measures in cardiac and pulmonary rehabilitation were presented by experts at a stakeholder consensus event and all stakeholders ( n = 18) were asked to (1) rank in order of importance a list of categories, (2) prioritise outcome measures and (3) prioritise baseline patient evaluation measures that should be assessed in a combined COPD and CHF rehabilitation programme. The tasks were completed anonymously and related to clinical rehabilitation programmes and associated research. Health-related quality of life, exercise capacity and symptom evaluation were voted as the most important categories to assess for clinical purposes (median rank: 1, 2 and 3 accordingly) and research purposes (median rank; 1, 3 and 4.5 accordingly) within combined exercise rehabilitation. All stakeholders agreed that profiling symptoms at baseline were 'moderately', 'very' or 'extremely' important to assess for clinical and research purposes in combined rehabilitation. Profiling of frailty was ranked of the same importance for clinical purposes in combined rehabilitation. Stakeholders identified a suite of multidisciplinary measures that may be important to assess in a combined COPD and CHF exercise rehabilitation programme.